Randomized clinical trial comparing survival after D1 or D2 gastrectomy for gastric cancer. Issue 2 (January 2014) - Degiuli, M.; Sasako, M.; Ponti, A.; Vendrame, A.; Tomatis, M.; Mazza, C.; Borasi, A.; Capussotti, L.; Fronda, G.; Morino, M.; Ferri, V.; Rebecchi, F.; et al.
<x xml:space="preserve">Abstract</x> Background It is still unclear whether D2 lymphadenectomy improves the survival of patients with gastric cancer and should therefore be performed routinely or selectively. The aim of this multicentre randomized trial was to compare D2 and D1 lymphadenectomy in the treatment of gastric cancer. Methods Between June 1998 and December 2006, patients with gastric adenocarcinoma were assigned randomly to either D1 or D2 gastrectomy. Intraoperative randomization was implemented centrally by telephone. Primary outcome was overall survival; secondary endpoints were disease‐specific survival, morbidity and postoperative mortality. Results A total of 267 eligible patients were allocated to either D1 (133 patients) or D2 (134) resection. Morbidity (12·0 versus 17·9 per cent respectively; P = 0·183) and operative mortality (3·0 versus 2·2 per cent; P = 0·725) rates did not differ significantly between the groups. Median follow‐up was 8·8 (range 4·5–13·1) years for surviving patients and 2·4 (0·2–11·9) years for those who died, and was not different in the two treatment arms. There was no difference in the overall 5‐year survival rate (66·5 versus 64·2 per cent for D1 and D2 lymphadenectomy respectively; P = 0·695). Subgroup analyses showed a 5‐year disease‐specific survival benefit for patients with pathological tumour (pT) 1 disease in the D1 group (98 per cent versus 83 per cent for the D2 group; P = 0·015), and for patients with pT2–4 status and positive lymph nodes in the D2 group (59 per cent versus 38 per cent for the D1 group; P = 0·055). Conclusion No difference was found in overall 5‐year survival between D1 and D2 resection. Subgroup analyses suggest that D2 lymphadenectomy may be a better choice in patients with advanced disease and lymph node metastases. Registration number: ISRCTN11154654 (http://www.controlled‐trials.com).